2012
DOI: 10.1142/s0219649212500098
|View full text |Cite
|
Sign up to set email alerts
|

The (Common) Sense of KM

Abstract: In 2002, Tom Wilson argued about knowledge management (KM) \that the bandwagon lacks wheels". In the same issue of the same journal, Leonard Ponzi and Michael Koenig posited that KM was perhaps \in the process of establishing itself as a new aspect of management". Who was correct? This article examines bibliographic evidence to conclude that the latter interpretation was correct, that KM has¯rmly established itself as a major, and to the extent that permanence can be established in this rapidly changing world,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Instead, they argue that KM exhibits attributes of a healthy academic domain with no apparent anomalies (Curado et al, 2011;Grant, 2011;Lee and Chen, 2012;Serenko et al, 2011b;. Recently, Koenig and Jank (2012) also concluded that KM has established itself as a major component of managerial practices. Therefore, it is more likely that KM has the potential to become a recognized field of science in the future.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Instead, they argue that KM exhibits attributes of a healthy academic domain with no apparent anomalies (Curado et al, 2011;Grant, 2011;Lee and Chen, 2012;Serenko et al, 2011b;. Recently, Koenig and Jank (2012) also concluded that KM has established itself as a major component of managerial practices. Therefore, it is more likely that KM has the potential to become a recognized field of science in the future.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…Apesar de sua evolução precoce, a GC ainda é um construto de maturação gradual (KOENIG;JANK, 2012;BONTIS, 2013;, para o qual se torna vital contribuir com a sua consolidação, inclusive, no âmbito da administração pública em educação, sendo esta a contribuição científica da pesquisa.…”
Section: Conclusõesunclassified
“…Affective commitment is of particular relevance to the emerging knowledge economy and to the knowledge firms (Casimir et al 2012), which entails that the study of Knowledge Management should broadly be done at the level of the Company which is the microlevel where Knowledge Management becomes critical. Another important corollary is that as the economy becomes more based on information and knowledge and upon information and knowledge-based products, the diffusion of technological and economic capability around the globe becomes more and more rapid (Koenig and Jank 2012). It has also been reported that 'many of the leading KM theories and practices recognize the importance of social interaction and communications in knowledge sharing and creation.…”
Section: Review Of Literaturementioning
confidence: 99%